Regionale Disparitäten in der Transformation: Braucht es ein Update der deutschen Regionalpolitik? - Jens Südekum; Daniel Posch (Wirtschaftsdienst, 2024)
– The green transition will affect different places in diverse ways, as place specific and contextual factors, such as pre-existing industrial specialisations, shape how transitions unfold in various territories. In the absence of a place-sensitive approach to decarbonisation, regional disparities are likely to intensify. This may make those who will be potentially hard hit reluctant to support policies necessary for reducing GHG-emissions. Research shows that populist parties that have been the most vocal opponents of climate policies in many countries can capitalize on this sentiment. Thus, investigating how both economic and political costs of the transition will be distributed regionally is key to crafting policies that make a just transition possible. By drawing on the findings of Südekum and Rademacher (2024), the text at hand discusses how the costs of the green transition are likely to be distributed among regions in Germany and what to do about it. It calls for a proactive approach to regional policy and outlines how Germany's most important regional policy programme can be updated.
Keywords: R11; Q56; 330; Regionalpolitik; Treibhausgas-Emissionen; Klimaneutralität; Deutschland; Regionalpolitik; Treibhausgas-Emissionen; Klimaneutralität; Deutschland